Latin American and Caribbean Regional Plan of Action on Population and Development (UN ECLAC SantiagoCL, 1996)
Identifies what is desirable for the region in relation to the links among population, development and the environment, and to progress in ensuring respect for human rights and correcting the inequality of living conditions observed among different social and ethnic groups, and geographic areas and between men and women.
DC